Getting tired of your friends: The dynamics of venture capital relationships - Du, Qianqian; Hellmann, Thomas (Journal of Financial Intermediation, 2024)
We empirically examine how venture capitalists adjust coinvestor relationships over time. We identify a fundamental trade-off where the benefits of familiarity are weighed against the opportunity costs of coinvesting with other syndication partners. Using US data, we find that venture capitalists dynamically adjust their relationship intensities by gradually disengaging from overly deep relationships. More centrally networked investors are more cautious with disengaging. In hot investment markets investors disengage more readily from existing relationships, but new relationships forged in hot market are less enduring. Perhaps surprisingly, we find a negative relationship between deeper prior relationships and investment performance.